Activitas, Formulasi dan Efektivitas Gel Ekstrak Beras Hitam (Oryza sativa L) terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Nur Khairi; Saldi Hapiwaty; Maulita Indrisari; Marwati Marwati (Postgraduate, University of Mataram, 2023)
Black rice (Oryza sativa L.) contains chemical compounds, namely ferulic acid, -oryzanol, amino acids, tannins, phenolics, and anthocyanins which have potential as antibacterial agents. This study aims to formulate an antibacterial gel preparation from black rice extract with an extract concentration of 10% and to test the antibacterial effectiveness of the gel preparation against Staphylococcus aureus and Escherichia coli bacteria. Black rice extract was obtained by maceration using 70% ethanol solvent: 3% citric acid. The extract obtained was then formulated in a gel dosage form. The results showed that black rice extract could be formulated as an antibacterial gel preparation that met the organoleptic, homogeneity, pH, spreadability, and adhesion requirements. In the results of the antibacterial effectiveness test, there is a clear zone which represents the ability to inhibit the growth of the tested bacteria by the gel. Black rice extract can be formulated in a gel dosage form with an extract concentration of 10% and a physically stable formula is obtained in formula III with a carbopol concentration of 2%. The average diameter of the antibacterial gel FIII preparation of black rice extract in inhibiting Staphylococcus aureus bacteria was classified as strong, namely 11.17 Â± 0.34 mm, while inhibition of Escherichia coli bacteria was also relatively strong, namely 12.20 Â± 0.46 mm